Antioxidant activity of two isomeric benzoxepin derivatives from the stem bark of Bauhinia Aculeata L. - Tanjung, Mulyadi (Journal of Chemical And Pharmaceutical Reseach 3/668 Ma;viya Nagar, Jalpur Rajasthan, India-302017, 2014)
Two benzooxepin types isolated from the stem bark of Bauhinia aculeata L. (Fabaceae) have been identified as bauhiniastin 4 (1) and pacharin (2). The structure of both compounds have been elucidated based on its spectroscopic data, including UV, 1D and 2D NMR, and HREISMS spectra. Compounds 1 – 2 were evaluated for their radical scavenging against 2,2-diphenyl-1-picrylhydrazyl (DPPH), showing their IC50 were 32.7, and 1495.2 µM, respectively. The results indicate that as bauhiniastin 4 (1) slightly more active than ascorbic acid (62.8 µM).